THE PARALLEL THE BETWEEN MOLDING OF EARLY PLACENTA AND HEART OF MAN - Абдул-Огли, Л.В. (World of Medicine and Biology, 2014)
A study exstraembryonic organ was conducted on embryos 4-8 weeks. Research was conducted on 34 embryos of man of prenatal ontogenesis, the reason of destruction of which was the artificial breaking of pregnancy on social testimonies at will of clinically healthy mother. For the duration of the embryonic period of ontogenesis, we determined laws governing the structural organization of the fibers of chorion within the standard. The special features of the structure of primary, second and tertiary fibers, and are also refined the periods of their forming were precise carried out the parallel between molding of early placenta and heart of man. The processes of the structural organization of heart and early placenta of man are tightly interconnected and it is only different in the temporary space. The development of early placenta anticipates the development of heart on the average to two weeks. Filling of fibers of chorion and the reduction of choriongel occurs unevenly and in this case were isolated three zones in the fibers of chorion, which differed in quantity and form of mesenchymal cells.